Improvising packet delivery and reducing delay ratio in mobile ad hoc network using neighbor coverage‐based topology control algorithm. (6th January 2020) - Rajakumari, K.; Punitha, P.; Lakshmana Kumar, R.; Suresh, C.
Summary: Mobile ad hoc network (MANET) is an infrastructure‐less network. Every Node act as a sender as well as receiver while sending a packet. Neighbor coverage probabilistic rebroadcasting (NCPR) protocol plays a momentous role in MANET for determining a route by helping the transitional nodes to onward a packet when the mobile nodes are not in the transmission space. This protocol minimizes the interference among node and increases the network capacity. There occurs a delay in the network while sending a packet via failure route or channel. Before sending a packet in the network, all the neighbor nodes have to be verified to avert congestion in the network. Quality of service (QoS) plays an important role in the development of MANET. In this research work, delay and neighbor connectivity‐based constrain is focused. The impact of node mobility during interference and delay is examined using network coding‐based topology control algorithm. By using this algorithm, irrelevant links are identified and detached from the topology. The simulation result shows that neighbor coverage established topology control algorithm for delay (NCTCAD) can reduce the delay and upturn the performance in MANETs. Abstract : The figure shows the graphical representation of neighbor coverage‐based topology control algorithm, which depends on the network layer. This algorithm is to fine‐tune the diffusion power that minimizes interference and selects a best optimal path for routing with efficient erasure coding to minimize the storage size for effective data delivery and also a contradictory to the requirement of delay constraint. The parameters used for computing the neighbor coverage ratio are energy, delay, link quality, and cost, which were helpful to obtain the best path, and also, topology was controlled, which makes high data delivery.